A-9-Years-Old Female with Diabetes Mellitus Type 1 with Hyperthyroidism - Puspa Sari, Ni Ketut; Mulyantari, Ni Kadek; Herawati, Sianny; Lestari, AA. Wiradewi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Diabetes Mellitus Type 1 (DMT1) and thyroid disease can occur together, which is defined as a variant of autoimmune polyglandular syndrome type 3. It is known that the action of insulin and thyroid hormones affect cellular metabolism, thyroid hormones contribute to carbohydrate metabolism and pancreatic function. Since the thyroid gland plays a central role in the regulation of metabolism, abnormal thyroid function can have a major impact on the control of diabetes and poor glycemic control can cause alterations in thyroid hormone. A female, 9 years old, with decreased consciousness. Previous medical history, polyuria, increased appetite, and drastic weight loss. She also complained of sweating even in a cold room and was often emotional. On physical examination, there was fever, shortness of breath, tachycardia, and a soft and diffused slightly enlarged thyroid gland, with no bruit on auscultation. Laboratory tests showed blood glucose levels at 739 mg/dL, HbA1c 9.2%, C-peptide 0.2 ng/mL, TSH levels 0.01 µIU/mL, FT4 levels 2.77 ng/dL, the presence of metabolic acidosis, proteinuria, glucosuria, and ketonuria. Thyroid dysfunction will have a negative effect on DM control while poor glucose control will harm the work of thyroid hormones. Improvement in glycemic control and routine insulin injection with the right dose will reduce the risk of diabetic vascular and metabolic complications onset and progression.